The changing of serum vitamin B-12 and homocysteine levels after gastrectomy in patients with gastric cancer: do they associate with clinicopathological factors? - Bilici, Ahmet; Sonkaya, Alper; Ercan, Şerif; Ustaalioğlu, Bala Başak Öven; Şeker, Mesut; Aliustao?lu, Mehmet; Orçun, Asuman; Gümüş, Mahmut (Springer, 2015)
After total (TG) or distal subtotal gastrectomy (DG), patients are at high risk of vitamin B-12 (vit-B-12) deficiency, which results in elevation of homocysteine levels. The changing of serum vit-B-12 and homocysteine levels in patients with gastric cancer is not well known. Seventy-two patients with gastric cancer who had undergone currative gastrectomy and 50 healthy controls were included. Serum vit-B-12 and homocysteine levels were analyzed in gastric cancer patients. In addition, these parameters were compared with those of healthy control subjects. While serum vit-B-12 levels in gastrectomized patients were significantly lower than that of healthy controls (221.8 +/- 125.6 pg/mL vs. 309.9 +/- 174.3 pg/mL, p = 0.002), homocysteine levels were significantly higher in patients with gastric cancer (14.2 +/- 6.7 mu mol/L vs. 12.5 +/- 6.1 mu mol/L, p = 0.016). Mean serum folate level was found to be high in healthy controls (7.3 ng/mL) compared to patients (9.2 ng/mL, p = 0.027). Out of 72 patients, 40 patients (55.6 %) with gastric cancer developed vit-B-12 deficiency after gastrectomy. Vit-B-12 deficiency was found to be related with gastrectomy type (p = 0.02) and homocysteine levels (p = 0.014). In patients who underwent TG, the incidence of vit-B-12 deficiency was significantly higher compared with those with DG (67.5 vs. 32.5 %). In addition, serum vit-B-12 level in patients with DG was significantly higher than that of patients with TG (248.3 +/- 122.0 pg/mL vs. 200.8 +/- 126.7 pg/mL, p = 0.041), whereas homocysteine levels were significantly lower in DG group compared with TG group (12.1 +/- 6.1 mu mol/L vs. 15.8 +/- 6.9 mu mol/L, p = 0.014). A logistic regression analysis showed that the extent of gastrectomy was found to be an independent factor for predicting the occurrence of vit-B-12 deficiency (p < 0.001, odds ratio 1.38). Our results showed that cumulative vit-B-12 deficiency rate was significantly higher after TG compared with that after DG, while homocysteine levels were significantly higher in TG group compared with DG group. The extent of gastrectomy was found to be an independent factor for predicting the occurrence of vit-B-12 deficiency. Vit-B-12 deficiency and hyperhomocysteinemia are imperious clinical situation for patients with gastric cancer after surgery. Hence, both preoperative and regular postoperative monitoring of vit-B-12 and homocysteine levels for all gastrectomized patients with gastric cancer are important and necessary for early detection and prevention of vit-B-12 deficiency and hyperhomocysteinemia as a risk factor for cardiovascular diseases.
WOS: 000350478200042
PubMed ID: 25296737
Keywords: Vitamin B-12; Homocysteine; Gastrectomy; Gastric Cancer